Discursive Thinking Through of Education Learning from Those Who Transform the Universe - Bazaluk, Oleg (Routledge International Studies in the Philosophy of Education, 2024)
This book is a contribution to the philosophical discourse on education. Education is considered a tool of philosophy. Education (paideia) and politics (politeia) are equal in importance for building a sustainable society free from feud and unhappiness. Discursive thinking through of education is based on Plato's dialogues and the results of epistemological, metaphysical and ethical research in the fields of cosmology, sociology and neuroscience. The author demonstrates the potential of the threefold scheme of philosophy, a Platone philosophandi ratio triplex, for ordering individual and collective discourse and way of life in strict accordance with the intelligible complexity of the expanding cosmos. An essential read for students and scholars interested in the crossroad between education and philosophy.